Pengaruh Olahraga Tradisional Terhadap Peningkatan Kebugaran Siswa Sdn Sidorejo 2 Ngawi - Abimanyu Perdana, Dewangga; Sudijandoko, Andun; Dzul Fikri, Muhammad; Candra Dewi, Ratna (Jurnal Porkes, 2024)
This study aims to determine the improvement of students' physical fitness whether there is an influence with traditional sports games. This research design is one-group pretest posttest design. The population was all students of SDN Sidorejo 2 Ngawi. The sample of this study was 20 students in grades IV and V. Instrument data is the TKJI test in children aged 10 to 12 years. Hypothesis testing used is the TKJI instrument test in children aged 10 to 12 years. Data analysis techniques using t-test analysis, swimmer normality and homogeneity tests, and hypothesis testing, are data analysis techniques. The t-test in hypothesis testing produces a t-count value of 3.538 which is greater than 1.730 on the t-table. (3,538 > 1,730). Therefore, there is a significant difference between the data before and after the treatment. The average value during the pretest was 12.40 and the average value for posttest data was 13.95. These results indicate that the level of physical fitness increased by 1.55 or 10.58% after the provision of traditional sports. In this case it can be said that the increase in students' physical fitness after learning through traditional sports is 10.58%. The conclusion is that the physical fitness of classes IV and V of Sidorejo 2 Ngawi State Elementary School increased after the provision of traditional sports.